Nasvay as a smokeless tobacco product - Abdyrakman, Eshiev (Medicine, law & society, 2025)
The purpose of the study is to evaluate the effect of nasvay on oral health in the Kyrgyz Republic. The study utilized a mixed-methods approach, combining a standardized questionnaire and dental examinations of 2,388 participants. It is determined that 32.9% of schoolchildren, 41.1% of students, and 35.7% of rural residents use nasvay. The prevalence rate is higher among men. The use of nasvay is associated with a high prevalence of dental diseases: leukoplakia, hyperaemia, and swelling of the mucous membrane. The index of caries, fillings, and lost teeth in users is 6.8. Among the methods of use, the most popular is in the cheek. It is discovered that the availability and low cost of nasvay contribute to its widespread use. The need for comprehensive preventive measures is emphasised, including increased regulation, educational campaigns, and reduction of economic dependence on the production of nasvay.
Keywords: leukoplakia; periodontal disease; precancerous dental lesions; smokeless tobacco; smokeless tobacco warnings; swelling of the mucous membrane